Comprehensive Emergency Obstetrical and Neonatal Care (CEmONC) at Karnali Academy of Health Sciences, Teaching Hospital, Jumla - Bhattarai, Saraswoti Kumari Gautam; Dahal, M. (Journal of Karnali Academy of Health Sciences, 2018)
Introduction: Providers skilled in emergency obstetric and newborn care (EmONC) services are essential, particularly in countries like Nepal with a high burden of maternal and newborn mortality. So this study aims to find out the status of comprehensive emergency obstetrical and neonatal care (CEmONC) service.Method: A retrospective cross-sectional study was conducted using secondary data sources at maternity ward of KAHS teaching hospital, Jumla. Total 291 women admitted in maternity ward for childbirth were included in the study of six month period of 2075. Sampling technique was census for the study who were admitted for child birth purpose. Cases were selected from the record of the maternity ward. The data was collected by using structured tool. Ethical approval was taken from the ethical review committee of KAHS for ethical clearance. Data was analyzed by using descriptive statistics.Result: There were 291 women admitted in the maternity ward for the purpose of childbirth during six-month period. Among them 224(76.97%) women delivered baby by spontaneous vaginal delivery; 61(20.96%) delivered with C/S and 6(2.06%) were delivered with instrumental delivery. Regarding the indication of 61 cesarean section (C/S) delivery; 22.95% with fetal distress, 16.39% with cephalopelvic disproportion and 11.47% with meconium stained liquorConclusions: About one third childbirth was done by cesarean section with indication of fetal distress, cephalo-pelvic disproportion and meconium stained liquor in higher proportion. Although CEONC service is effective, the rate of cesarean section can be reduced by providing good quality antenatal care.